Soviet Socio-Cultural Practices from Perspective of Genres in Pioneer Magazine - T. V. Dubrovskaya (Научный диалог)
The article presents some results of the project that is aimed at constructing a mediatised model of the Soviet society in periodicals for children. The data has been drawn from the Pioneer magazine published in the 1970s. This paper focuses on its structure and contents, as well as typical genres that construct the representations of the Soviet society and socio-cultural practices. The degree of ideology is defined that characterises various genres. In terms of methodology, the study draws on constructivism, critical discourse analysis, theory of journalistic genres, theory of speech genres, and semiotic analysis. Genres are interpreted based on their ideological charge, types of socio-cultural practices they represent, and the semiotic resources employed. The findings show that the ideological charge can be graded from being non-existent to dominating the factual information. The ideological component is secondary in genres of popular science and general education, whereas genres that reproduce adults’ institutional socio-political practices demonstrate a high degree of ideological charge, which is conveyed through specific semiotic resources. At the same time, the magazine adapts the representations of Soviet values for adolescents through the use of everyday language and visual images of routine life.